Predicting statistics performance beyond statistics anxiety - Kwek, Kenneth Shuan Gui (2017)
Statistics anxiety has been the focus of past researchers seeking to improve students’ statistics performance. Recent research has challenged the widely-held assumption that statistics anxiety would negatively predict statistics performance. This study investigated the predictive value of goal orientation, statistics self-efficacy, learning strategies, and learning emotions relative to the influence of statistics anxiety on statistics performance. A total of 115 participants completed a questionnaire which included five measures adapted from PALS, MSLQ, CSSE, LRE and STARS. Hierarchical regression analyses revealed that mastery goal orientation and learning hopelessness were the strongest predictors of statistics performance after controlling for “worth of statistics”, self-regulation and pride. Specifically, mastery goal orientation positively predicted statistics performance whereas learning hopelessness negatively predicts statistics performance. Implications for the research of statistics anxiety are discussed and recommendations for interventions by statistics instructors are presented.